Upaya Guru Dalam Memaksimalkan Perkembangan Kognitif, Sosial dan Motorik Anak Usia Dini - Muhammad Khoiruzzadi; Mabid Barokah; Aisiyatin Kamila (JECED : Journal of Early Childhood Education and Development, 2020)
Teachers are the spearhead in maximizing early childhood development. The purpose of this study is to determine the efforts of teachers in developing children's potential, and want to know the obstacles experienced by teachers on children's cognitive, social and motor development. this research included in field research (field research). The approach used is a descriptive qualitative approach. For primary data is data obtained from interviews with class B1 group teachers and school principals, as well as the results of observations of learning both inside and outside class B1 group RA Ar-Rahmah Papringan Caturtunggal, Depok District, Sleman Regency. The results showed that teachers need to understand the ideal development of a child in terms of cognitive, social and motor aspects. RA Ar-Rahmah group B1 has different character and development, some are smart in counting, active in moving and playing, active in answering, responsive to teachers and friends, and others. The learning done by teachers in group B1 children is more varied in using learning methods such as singing, habituation, exemplary, advice, and others in accordance with what material is intended to be taught to children. Interlude between one material with another learning material is also important in learning conducted at RA Ar-Rahmah. Excellent programs owned by RA Ar-Rahmah also encourage teachers to think together so that the desired goals of the school are achieved. Developmental delay in children is indeed one of the obstacles in optimizing children's development. The need for good collaboration between teachers at school and parents at home in optimizing children's cognitive, social and motor development.